Non-equilibrium thermodynamics in electrochemical complexation of Li–oxygen porous electrodes. Issue 15 (22nd March 2019) - Mistry, Aashutosh N.; Cano-Banda, Fernando; Law, Dickens; Hernandez-Guerrero, Abel; Mukherjee, Partha P.
Abstract : The non-equilibrium mechanistics, resulting from concentrated electrolyte transport and porous structure assisted convolution of interactions, are examined for Li–oxygen electrodes. Abstract : The lithium–oxygen conversion chemistry relies on solid-electrolyte interface centered energy storage, rather than bulk considerations in intercalation chemistry. The electrochemical complexations in porous air electrodes are, however, a manifestation of coupled interface-transport-kinetic interactions. The non-equilibrium thermodynamics behind such multi-modal coupling, hitherto unappreciated, forms the central argument of this work. We comprehensively demonstrate the role of reciprocity between electrode architecture and off-equilibrium interactions in Li–O2 electrochemistry based energy storage.